The Development of Energy in East Europe - Polach, J.G. (Washington D.C.: Resources for the Future, Inc., 1970)
This study examines the development of energy in East Europe from 1950 through 1970. Its purpose is to analyze and evaluate the role of energy within the area as a whole and in its component countries, especially with respect to the implications of the development of energy for economic growth, trade, and ultimately economic welfare of the people of the area.
Reprinted from Economic Developments in Countries of Eastern Europe, A compendium of papers submitted to the Subcommittee on Foreign Economic Policy of the Joint Economic Committee, 91 Cong. 2 sess. (1970).
ne 26/04/2018
Loans
Keywords: Power Resources; Energy policy